Method for synthesizing nanoscale single crystal lithium-rich manganese-based positive electrode material by molten salt method

Synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode material through the molten salt method solves the conductivity and stability problems caused by the large particle size of traditional materials, and achieves the improvement of the nanoification and electrochemical performance of the materials.

CN119507024APending Publication Date: 2025-02-25湖南鹏博新材料有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411678074.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have large particle sizes, resulting in poor electron and ion conductivity, and limited solid-solid interface contact, affecting the dynamic performance and structural stability of the material.

Method used

The nano-scale single crystal lithium-rich manganese-based positive electrode material was synthesized by the molten salt method. By controlling the calcining temperature and the addition of molten salt, nano-scale particles of 300-700nm were obtained, avoiding multiple high-temperature sintering to form uniformly distributed single crystal particles.

Benefits of technology

The nanoification of the material is achieved, the Li+ diffusion distance is shortened, the grain boundary affects the diffusion of lithium ions is avoided, and the electrochemical reaction active area and cycling stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507024A_ABST
    Figure CN119507024A_ABST
Patent Text Reader

Abstract

The invention provides a method for synthesizing a nanoscale single crystal lithium-rich manganese-based positive electrode material by a molten salt method. The method comprises the following steps: 1, sequentially pouring deionized water and a complexing agent aqueous solution into a continuous stirred tank reactor; 2, pumping a mixed metal salt solution of a nickel source, a cobalt source and a manganese source and a precipitator, continuously stirring at a certain temperature, aging, and carrying out suction filtration, washing and drying to obtain a carbonate precursor; and 3, mixing the carbonate precursor and a lithium source according to a certain stoichiometric ratio, adding molten salt, and calcining and washing the powdery mixture to obtain the nano-scale single-crystal lithium-rich manganese-based positive electrode material. According to the method, the nanoscale single crystal particles can be directly formed, so that the Li < + > diffusion distance is effectively shortened, the influence of a grain boundary on lithium ion diffusion is avoided, and the electrochemical reaction active area is increased; and the material also has a more favorable microstructure, and material structure deterioration caused by an electrochemical-mechanical effect in a battery cycle process is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery material preparation, and in particular to a method for synthesizing a nano-scale single crystal lithium-rich manganese-based positive electrode material using a molten salt method. Background Art

[0002] With the increasing demand for high-energy-density, low-cost lithium-ion batteries (LIBs) in modern society, the traditional high-voltage LiCoO 2 The high nickel layered cathode materials have limited specific capacity (<230 mAh g -1 ) and resource shortages make it difficult to meet the requirements. Lithium-rich manganese-based layered oxides (xLi) with dual redox properties of transition metal (TM) cations and oxygen anions 2 MnO 3 (1-x)LiTMO 2 , LRMO) is considered to be the most promising cathode material for the next generation. However, the commercial application of LRMO still faces some technical bottlenecks. The traditional polycrystalline lithium-rich manganese-based cathode material (PC-LRMO) has a large particle size (about 10-20μm), which is bound to affect the utilization of active materials due to its poor electronic and ionic conductivity and the limitation of solid-solid interface contact. Therefore, in order to improve the performance of LRMO, it is necessary to further optimize the material particle size and morphology and rationally design the structure of the composite cathode. Summary of the invention

[0003] The purpose of the present invention is to provide a method for synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode materials by a molten salt method, so as to solve the problems of large particle size, poor electronic and ionic conductivity, limitation of solid-solid interface contact, dynamic performance and structural stability of LRMO materials in the prior art. This molten salt method can promote the growth of grains, and nano-scale particles can be obtained while controlling the calcination temperature, eliminating the ultra-high temperature calcination and multiple calcinations of the conventional method, which is more convenient, energy-saving and environmentally friendly, and can reduce the voltage drop during the cycle and improve the cycle stability.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A method for synthesizing a nano-scale single-crystal lithium-rich manganese-based positive electrode material by a molten salt method comprises the following steps:

[0006] The first step: pouring deionized water and complexing agent aqueous solution into a continuous stirred tank reactor in sequence;

[0007] Step 2: Pump a mixed metal salt solution of nickel source, cobalt source, manganese source and a precipitant into a continuous stirred tank reactor, continuously stir and age at a certain temperature, and then obtain a carbonate precursor by suction filtration, washing and drying;

[0008] Step 3: Mix the carbonate precursor and the lithium source in a certain stoichiometric ratio, add molten salt, and then calcine and wash the powdery mixture formed by mixing the carbonate precursor, the lithium source and the molten salt to obtain a nano-scale single crystal lithium-rich manganese-based positive electrode material.

[0009] In one embodiment, the chemical formula of the carbonate precursor is (Ni 1 / 6 Co 1 / 6 Mn 4 / 6 )CO 3 .

[0010] In one embodiment, the lithium source is one or both of lithium carbonate and lithium hydroxide.

[0011] In one embodiment, the amount of the lithium source added is such that the weight ratio of lithium ions to transition metal ions in the carbonate precursor is 1.5-1.6:1.

[0012] In one embodiment, the molten salt is one or more of potassium chloride, sodium chloride, and lithium chloride.

[0013] In one embodiment, the calcination time in the third step is 8 to 12 hours, and the temperature is between 900-1000°C.

[0014] In one embodiment, the nano-scale single crystal lithium-rich manganese-based positive electrode material has a grain size of 300-700 nm and a chemical formula of Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O 2 , abbreviated as SC-LRMO.

[0015] In one embodiment, the complexing agent is a soluble salt with ammonium ions, the nickel source, cobalt source, and manganese source are corresponding water-soluble salts, and the precipitant is a water-soluble carbonate.

[0016] In one embodiment,

[0017] Step 1: Pour 1L of deionized water and 100mL of complexing agent aqueous solution into a continuous stirred tank reactor in sequence;

[0018] Step 2: Pump 500 mL of 2 mol L -1 of mixed metal salt solution and 500 mL of 2 mol L -1 Sodium carbonate solution, Ni in the mixed metal salt solution 2+ :Co 2+ :Mn 2+The molar ratio of the reaction mixture is 1:1:4, and then the mixture is stirred at 60°C for 20 hours and aged for 5 hours, and then filtered, washed and dried to obtain a carbonate precursor;

[0019] Step 3: Mix 10% wt of lithium carbonate as a lithium source with the carbonate precursor formed in the second step, add three times the total molar amount of lithium chloride as a molten salt, and heat the mixture in air at 920°C for 10 h at a heating rate of 4°C min -1 After high-temperature reaction, the mixture is washed with deionized water to remove excess salt, taken out, ground and sieved to obtain a nano-scale single crystal lithium-rich manganese-based positive electrode material.

[0020] Compared with the prior art, the present invention has the following advantages or beneficial effects:

[0021] (1) The present invention limits the range and amount of molten salt added. Such molten salt can improve the dispersibility of the grains, will not have side reactions with the material itself during the calcination process, and can be removed by simple water washing; if too much molten salt is added, the amount of deionized water used in the washing process will increase and the washing difficulty will increase, and the residual molten salt will also affect the electrochemical properties of the product; if too little is added, the grain dispersion effect is poor and nano-scale particles cannot be achieved;

[0022] (2) The present invention limits the amount of lithium source added. If the lithium source is added according to the standard molar ratio or the amount added is too small, the lithium source will volatilize during the calcination process, resulting in insufficient lithium ratio; if the amount added is too large, the reaction will be incomplete, affecting the performance of the final product;

[0023] (3) The present invention limits the calcination temperature. If the temperature is too low, the crystallinity of the product will not be high and it will cause Li + / Ni 2+ The mixing degree is too high; if the temperature is too high, the particle size of the product will increase with the increase of temperature, and when a certain temperature is reached, octahedral particles, namely spinel phase, will be formed;

[0024] (4) The present invention provides a method for synthesizing a nano-scale single-crystal lithium-rich manganese-based positive electrode material by a molten salt method. The use of the molten salt method to prepare a nano-scale single-crystal lithium-rich manganese-based positive electrode material can avoid multiple high-temperature sintering to form primary grains with uniform particle distribution. Compared with traditional secondary polycrystalline particles, this small-sized single-crystal lithium-rich positive electrode not only effectively shortens the Li + Diffusion distance, avoiding the influence of grain boundaries on lithium ion diffusion, and increasing the active area of ​​electrochemical reaction;

[0025] (5) The present invention provides a method for synthesizing nano-scale single-crystal lithium-rich manganese-based positive electrode materials by a molten salt method. The nano-scale single-crystal lithium-rich manganese-based positive electrode materials prepared by the molten salt method have a primary particle size of 300-700nm. Compared with other single-crystal nanomaterials prepared by multiple sintering, the preparation process of the present invention is simple and the temperature is relatively low. It can be nanosized and has a more favorable microstructure, which helps to alleviate the material structure degradation caused by the electrochemical-mechanical effect during the battery cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is the SEM picture of the embodiment and comparative example in the present invention;

[0027] Figure 2 It is a magnification diagram of the embodiments and comparative examples in the present invention at 0.1C-5C;

[0028] Figure 3 The cross-sectional SEM images of the embodiments and comparative examples of the present invention after 100 cycles. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example:

[0031] 1L of deionized water and 100mL of complexing agent aqueous solution were poured into the continuous stirred tank reactor in sequence, and then 500mL / 2mol L -1 Mix metal salt solution and 500mL / 2mol L -1 Sodium carbonate solution, Ni in the above mixed metal salt solution 2+ :Co 2+ :Mn 2+ The molar ratio between the two is 1:1:4, and then the mixture is stirred continuously at 60°C for 20 hours and aged for 5 hours; then an excess of 10% wt of lithium carbonate as a lithium source is mixed with the above carbonate precursor, and lithium chloride is added as a molten salt with a total molar amount of three times that of the lithium carbonate and the carbonate precursor, and the mixture is heated in air at 920°C for 10 hours at a heating rate of 4°C min -1 After high temperature reaction, the mixture was washed with deionized water to remove excess salt, and then taken out and ground and sieved to obtain nano-scale SC-LRMO.

[0032] Comparative Example:

[0033] 1L of deionized water and 100mL of complexing agent aqueous solution were poured into the continuous stirred tank reactor in sequence, and then 500mL / 2mol L -1 Mix metal salt solution and 500mL / 2mol L -1 Sodium carbonate solution, Ni in the above mixed metal salt solution 2+ :Co 2+ :Mn 2+ The molar ratio between them is 1:1:4, and then stirring is continued at 60°C for 20 hours and aged for 5 hours. Then, an excess of 10% wt of lithium carbonate as a lithium source is mixed with the above-mentioned carbonate precursor, and then the mixture is calcined at 500°C for 5h, and then at 900°C for 22h. After taking out, it is ground and sieved to obtain a secondary particle polycrystalline material PC-LRMO.

[0034] The following table shows the test data of the embodiments and comparative examples:

[0035]

[0036] By comparing the data in the above table, it can be seen that the addition of the primary single crystal material synthesized by molten salt has a great influence on the electrochemical performance. In the embodiment, the primary grain size of the nano-scale single crystal lithium-rich manganese-based positive electrode material reaches about 300-700nm, and the 0.05C discharge capacity is about 316mAh / g, reaching a very excellent level;

[0037] like Figure 1-3 As shown in the figure: By comparing the cross-sectional SEM images after 100 cycles, it can be found that PC-LRMO has obvious intergranular cracks, while SC-LRMO particles still show good particle integrity; this is because the grain boundaries of primary particles of polycrystalline materials will accumulate more local stress during the cycle. On the contrary, single crystal particles have no grain boundaries and can better transmit and disperse stress, thereby inhibiting adverse electrochemical-mechanical effects such as particle breakage and cathode / electrolyte contact loss, and ultimately improving the electrochemical performance (reversible capacity, rate performance and cycle stability).

[0038] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.

[0039] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode materials by a molten salt method, characterized in that: The following steps are involved: The first step: pouring deionized water and complexing agent aqueous solution into a continuous stirred tank reactor in sequence; Step 2: Pump a mixed metal salt solution of nickel source, cobalt source, manganese source and a precipitant into a continuous stirred tank reactor, continuously stir and age at a certain temperature, and then obtain a carbonate precursor by suction filtration, washing and drying; Step 3: Mix the carbonate precursor and the lithium source in a certain stoichiometric ratio, add molten salt, and then calcine and wash the powdery mixture formed by mixing the carbonate precursor, the lithium source and the molten salt to obtain a nano-scale single crystal lithium-rich manganese-based positive electrode material.

2. The method for synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode materials by a molten salt method according to claim 1, characterized in that: The chemical formula of the carbonate precursor is (Ni 1 / 6 Co 1 / 6 Mn 4 / 6 )CO3.

3. The method for synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode materials by a molten salt method according to claim 1, characterized in that: The lithium source is one or both of lithium carbonate and lithium hydroxide.

4. The method for synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode materials by a molten salt method according to claim 1, characterized in that: The amount of lithium source added is such that the weight ratio of lithium ions to transition metal ions in the carbonate precursor is 1.5-1.6:

1.

5. The method for synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode materials by a molten salt method according to claim 1, characterized in that: The molten salt is one or more of potassium chloride, sodium chloride and lithium chloride.

6. The method for synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode materials by a molten salt method according to claim 1, characterized in that: The calcination time in the third step is 8 to 12 hours, and the temperature is between 900 and 1000°C.

7. The method for synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode materials by a molten salt method according to claim 1, characterized in that: The nano-scale single crystal lithium-rich manganese-based positive electrode material has a grain size of 300-700 nm and a chemical formula of Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

8. The method for synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode materials by a molten salt method according to claim 1, characterized in that: The complexing agent is a soluble salt with ammonium ions, the nickel source, the cobalt source and the manganese source are corresponding water-soluble salts, and the precipitant is a water-soluble carbonate.

9. The method for synthesizing nano-scale single crystal lithium-rich manganese-based positive electrode materials by a molten salt method according to claim 1, characterized in that: Step 1: Pour 1L of deionized water and 100mL of complexing agent aqueous solution into a continuous stirred tank reactor in sequence; Step 2: Pump 500 mL of 2 mol L -1 of mixed metal salt solution and 500 mL of 2 mol L -1 Sodium carbonate solution, Ni in the mixed metal salt solution 2+ :Co 2+ :Mn 2+ The molar ratio of the reaction mixture is 1:1:4, and then the mixture is stirred at 60°C for 20 hours and aged for 5 hours, and then filtered, washed and dried to obtain a carbonate precursor; Step 3: Mix 10% wt of lithium carbonate as a lithium source with the carbonate precursor formed in the second step, add three times the total molar amount of lithium chloride as a molten salt, and heat the mixture in air at 920°C for 10 h at a heating rate of 4°C min -1 After high-temperature reaction, the mixture is washed with deionized water to remove excess salt, taken out, ground and sieved to obtain a nano-scale single crystal lithium-rich manganese-based positive electrode material.

Citation Information

Cited By

  • Method for preparing single-crystal-state lithium-rich manganese-based positive electrode material by molten salt method, positive electrode material prepared by method, positive electrode and battery

    CN120914242A

  • Method for producing positive electrode active material, positive electrode active material, positive electrode, and power storage device

    WO2026191339A1